Repeatability and Reproducibility of 4.5 by 4.5 mm Peripapillary Optical Coherence Tomography Angiography Scans in Glaucoma and Non-Glaucoma Eyes. Issue 9 (16th June 2022) - Shen, Alena J.; Urrea, Anna L.; Lee, Jae Chang; Burkemper, Bruce; LeTran, Vivian H.; Zhou, Xiao; Chu, Zhongdi; Grisafe, Dominic J.; Fard, Ali; Wong, Brandon; Song, Brian; Xu, Benjamin Y.; et al.
Abstract : Précis: Peripapillary vessel parameters from optical coherence tomography angiography (OCTA) 4.5×4.5 mm scans in nonglaucomatous and glaucomatous eyes showed high repeatability and reproducibility, with higher reliability for commercially developed OCTA parameters compared with custom OCTA parameters. Purpose: The purpose of this study was to assess intrasession repeatability versus intersession reproducibility of peripapillary vessel parameters from 4.5×4.5 mm OCTA scans in nonglaucomatous eyes and glaucomatous eyes. Materials and Methods: In a longitudinal study, peripapillary OCTA scans were quantified using research-oriented custom quantification software that calculated vessel area density (VAD) and flux and clinic-oriented commercially developed software (Cirrus 11.0) that calculated perfusion density (PD) and flux index (FI). Intrasession repeatability and intersession reproducibility were evaluated using within-eye coefficient of variation (CVW ) and intraclass correlation coefficient (ICC). Results: With 127 nonglaucomatous eyes, intrasession CVW for VAD, PD, flux, and FI were 1.900%, 1.174%, 2.787%, and 1.425%, respectively. The intersession CVW were 2.039%, 1.606%, 4.053%, and 2.798%, respectively. Intrasession ICC ranged from 0.903 to 0.956, and intersession ICC ranged from 0.850 to 0.896. Among 144 glaucomatous eyes, intrasession CVW for VAD, PD, flux, and FI were: 3.841%, 1.493%, 5.009%, and 2.432%, respectively. The intersession CVW were 4.991%, 2.155%, 6.360%, and 3.458%, respectively. Intrasession ICC ranged from 0.956 to 0.969, and intersession ICC ranged from 0.918 to 0.964. Conclusions: Among nonglaucomatous and glaucomatous eyes, the majority of peripapillary OCTA vessel parameters from 4.5×4.5 mm scans had greater intrasession repeatability than intersession reproducibility. There was a greater agreement for the commercially developed quantification parameters than for their custom quantification counterparts.